(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2010)
One of the efforts to increase the quality and production of cacao is to apply proper technology of cacao production at farmers level. Level of the technology of cacao production is different among the farmers, which related to the motivation. The present research objectives were to identify motivation of farmers in implementing the cacao production technology, to identify the implementation of the cacao production technology by farmers, to analyze the factors of farmers’ motivation in implementing the cacao production technology, and to analyze motivation of farmers in implementing the cacao production technology. The research method used was descriptive-correlation. The population consisted of 40 cacao farmers in Sirenja District, Donggala Regency, Central Sulawesi Province, while the data collection was conducted on census basis. The data collection was carried out from June until August 2008. The analysis of the data was performed using the correlation test of Tau-b-Kendall. The results showed that motivation of cacao farmers was at middle level. The implementation of cacao production technology was at middle level which means that cacao farmers often apply the technology. Several farmer’s characteristics which significantly correlated with motivation were the area of land for cultivation, information access, availability of utility and infrastructure, and the characteristic of innovation. Intrinsic motivation of cacao farmers was closely related to the implementation of cacao production technology. Key words: motivation, cacao farmer, cacao, production technology.